Service quality measurement model integrating an extended SERVQUAL model and a hybrid decision support system - Abteen Ijadi Maghsoodi; Abbas Saghaei; Ashkan Hafezalkotob (European Research on Management and Business Economics (ERMBE), 2019)
One of the most effective solutions to sustain an organization in competitive environments is the strategy of continuous improvement. Consequently, the proposed strategy needs a continuous performance evaluation measurements. A solution to evaluate service quality measurements is to rank the service providers. The ranking procedure in similar complex problems or selection problems can be efficiently implemented with the support of multiple attribute decision making (MADM) methods. This study aims at developing a comprehensive decision support system (DSS) based on multiple MADM methods along with an extended quality of service evaluation model to assess the service quality of certain cultural centers. The suggested service quality measurement model in this study is recognized as a valid and reliable tool based on statistical modeling and validation methods. Moreover, the suggested DSS model has been developed based on integration of target-based F-MULTIMOORA and Fuzzy Axiomatic Design (FAD) methods combined with the best-worst method (BWM). Accordingly, a case study was investigated regarding the assessment of seven art galleries in Tehran, Iran. Ultimately, an extensive managerial investigation of the DSS model has been presented based on the real-world examples to show the practicality of the propositions of the current study.
Keywords: 650; Service quality; Art galleries; Decision support system (DSS); Fuzzy Axiomatic Design (FAD); F-MULTIMOORA; Best-worst method (BWM); Target-based attributes